REFORMULASI KURIKULUM PENDIDIKAN ISLAM DALAM ERA DISRUPSI DIGITAL - Aziza, Ilma Fahmi (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
The era of digital disruption, marked by the emergence of new technologies, has changed almost all aspects of life, including the way humans learn and teach. Islamic education, as a system that has a long tradition in transmitting knowledge and religious values, faces great challenges to adapt to this new reality. The research approach used in this study is a qualitative approach to explore in-depth understanding of the impacts, challenges, and solutions related to digital disruption in Islamic education. The qualitative approach was chosen because this study aims to understand the complex phenomena involving the adaptation of Islamic education to technological changes, as well as identifying relevant solutions in social and religious contexts. The results of this study conclude that although the era of digital disruption brings many challenges, there is a great opportunity to reformulate Islamic education in an innovative and effective way. This reformulation must include the development of technological infrastructure, validation of religious content, the implementation of blended learning models, and increasing digital literacy for educators. By adopting a wise approach, Islamic education can remain relevant and continue to develop in the digital era, without abandoning the core values ​​of religious teachings. In the reformulation of the Islamic Education curriculum, learning about digital ethics also needs to be integrated into the curriculum so that students can become responsible technology users, who do not only use technology for personal gain, but also for the common good in accordance with Islamic teachings.